You Don't Like the Truth - 4 Days In Guantánamo - Côté, Luc; Henriquez, Patricio (Les Films Adobe, 2010)
Verzio FF Duration: 01:40:00 A poorly recorded video starts. Behind the table a young prisoner in chains and dressed in orange sits waiting. This is Canadian Omar Khadr who became - at 15 - the only child prisoner at a US maximum security facility in Guantánamo Bay, Cuba. In February 2003 Omar met investigators from the Canadian secret services during a four-day interrogation, mapped out in this documentary. The entire encounter was recorded. In May, 2008, the Canadian Supreme Court ordered the Canadian government to turn over to Omar Khadr's lawyers thousands of pages of documents related to the case, and so seven hours of videotape entered the public domain. With this unique document as the backbone of the documentary, the interrogation is examined by a panel of experts including a Toronto psychiatrist who specializes in treating torture victims , and the US military defense lawyer representing Omar Khadr. He is to be the first child soldier ever to be charged with war crimes.